2019
DOI: 10.1038/s12276-019-0287-2
|View full text |Cite
|
Sign up to set email alerts
|

Anoctamin 1/TMEM16A controls intestinal Cl− secretion induced by carbachol and cholera toxin

Abstract: Calcium-activated chloride channels (CaCCs) mediate numerous physiological functions and are best known for the transport of electrolytes and water in epithelia. In the intestine, CaCC currents are considered necessary for the secretion of fluid to protect the intestinal epithelium. Although genetic ablation of ANO1/TMEM16A, a gene encoding a CaCC, reduces the carbachol-induced secretion of intestinal fluid, its mechanism of action is still unknown. Here, we confirm that ANO1 is essential for the secretion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 62 publications
2
22
0
Order By: Relevance
“…In our own previous studies (Ousingsawat et al, 2009; Schreiber et al, 2010; Ousingsawat et al, 2011; Kunzelmann and Schreiber, 2014; Schreiber et al, 2015; Benedetto et al, 2017; Benedetto et al, 2019a, b), and in reports by other teams (Gomez-Pinilla et al, 2009; He et al, 2011; Hoque et al, 2012; Mroz and Keely, 2012; Yin et al, 2017; Rottgen et al, 2018; Lee et al, 2019), expression of Tmem16a in murine intestine was convincingly demonstrated. A gradual decrease of expression from distal colon toward small intestine was shown previously (Wanitchakool et al, 2014).…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…In our own previous studies (Ousingsawat et al, 2009; Schreiber et al, 2010; Ousingsawat et al, 2011; Kunzelmann and Schreiber, 2014; Schreiber et al, 2015; Benedetto et al, 2017; Benedetto et al, 2019a, b), and in reports by other teams (Gomez-Pinilla et al, 2009; He et al, 2011; Hoque et al, 2012; Mroz and Keely, 2012; Yin et al, 2017; Rottgen et al, 2018; Lee et al, 2019), expression of Tmem16a in murine intestine was convincingly demonstrated. A gradual decrease of expression from distal colon toward small intestine was shown previously (Wanitchakool et al, 2014).…”
Section: Introductionsupporting
confidence: 63%
“…The present and previous data indicate expression of Tmem16a in murine colonic epithelium. Tmem16a controls Ca 2+ and cAMP-activated Cl – transport (Schreiber et al, 2015; Benedetto et al, 2017; Lee et al, 2019). In contrast, Vega et al (2019) reported lack of expression of Tmem16a in murine intestinal epithelium, and did not detect a difference in Ca 2+ - and cAMP-activated transport between WT and Tmem16a knockout animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stimulated I sc in control tissues was reduced 80% by postapplication of R-BPO-27, suggesting that the remaining 20% of I sc was dependent on other Clchannels, such as ANO1 expressed in the villus apical membrane. 32 In MYO5Bknockout jejunum from mice with vehicle or og LPA administration, R-BPO-27 decreased I sc more than the values of forskolin-evoked I sc increase, consistent with the abnormal basal CFTR activity. Administration of IP LPA or GRI977143 suppressed basal CFTR activity, but cAMPactivated I sc was completely reversed by R-BPO-27, indicating that LPAR2 activation did not alter CFTR expression ( Figure 2E and F).…”
Section: Lpa Suppressed Endogenous Hyperactivity Of Cftr and Increasementioning
confidence: 76%
“…Subsequently, multiple studies showed the induction of ANO1-mediated CaCC by GPCR agonists in cells with endogenous expression of ANO1 and corresponding GPCRs. Some examples include angiotensin II in cardiac fibroblasts (El Chemaly et al, 2014), basilar artery smooth muscle cells (Li R. S. et al, 2016), and human umbilical vein endothelial cells HUVEC (Ma et al, 2017); endothelin-1 in dorsal root ganglion (DRG) neurons (Cho et al, 2012); epinephrine in Calu-3 human bronchial serous cell model (Banga et al, 2014); carbachol in intestinal epithelial cells (Lee et al, 2019) and in dorsal root ganglion (DRG) neurons (Cho et al, 2012); bradykinin and histamine in DRG neurons (Liu et al, 2010;Cho et al, 2012); and extracellular ATP in FRTL-5 thyroid cells (Iosco et al, 2014). The contribution of ANO1 to CaCC in these studies was determined using pharmacological inhibitors of ANO1 (i.e., T16A inh -A01) (Namkung et al, 2011a), siRNA-mediated ANO1 knockdown, or ablation of ANO1 gene.…”
Section: Physiological and Pathological Activators Of Ano1-mediated Cmentioning
confidence: 99%